2016
DOI: 10.3390/s16111856
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Portable SPR Bioanalyzer for Sensitive Detection of Escherichia coli O157:H7

Abstract: The purpose of this study was to develop a portable surface plasmon resonance (SPR) bioanalyzer for the sensitive detection of Escherichia coli O157:H7 in comparison with an enzyme-linked immunosorbent assay (ELISA). The experimental setup mainly consisted of an integrated biosensor and a homemade microfluidic cell with a three-way solenoid valve. In order to detect Escherichia coli O157:H7 using the SPR immunoassay, 3-mercaptopropionic acid (3-MPA) was chemisorbed onto a gold surface via covalent bond for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In recent years, many studies have reported the application of SPR biosensors in the detection of O157:H7, S. enteritidis , and L. monocytogenes (Nanduri and others ; Liu and others ; Wang and others ). Nanduri and others () applied a SPREETA3 TM biosensor for the detection of L. monocytogenes using phage‐displayed antibody and the detection limit for L. monocytogenes in buffer was estimated to be 2.0 × 10 6 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have reported the application of SPR biosensors in the detection of O157:H7, S. enteritidis , and L. monocytogenes (Nanduri and others ; Liu and others ; Wang and others ). Nanduri and others () applied a SPREETA3 TM biosensor for the detection of L. monocytogenes using phage‐displayed antibody and the detection limit for L. monocytogenes in buffer was estimated to be 2.0 × 10 6 CFU/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Nanduri and others () applied a SPREETA3 TM biosensor for the detection of L. monocytogenes using phage‐displayed antibody and the detection limit for L. monocytogenes in buffer was estimated to be 2.0 × 10 6 CFU/mL. Wang and others () developed a portable SPR biosensor for sensitive detection of O157:H7 and the theoretical detection limit of 1.87 × 10 3 CFU/mL was calculated from the positive control samples. The detection format used with SPR biosensor in both studies is direct detection, which may contribute to the high detection limits.…”
Section: Resultsmentioning
confidence: 99%
“…These are intrinsic problems in the conventional SPR methods. For the extension of SPR applications to food safety, either new surfaces [ 28 , 29 , 30 ] have been tested or new portable instruments have been developed [ 31 ].…”
Section: Spr Methodsmentioning
confidence: 99%
“…The unlabeled characteristic of the device can ensure its reproducibility. At present, the device is being further miniaturized to facilitate POCT [ 103 ]. Demirci et al [ 32 ] prepared a portable, multichannel, and inexpensive microfluidic-integrated SPR platform which can quickly detect and quantify bacteria, namely E. coli and S. aureus .…”
Section: Biosensor-based Microfluidics For the Detection Of Foodborne Pathogenic Bacteriamentioning
confidence: 99%